Sosialisasi Pentingnya Pencegahan Narkoba Jenis Sabu-Sabu Bagi Pemuda - Moh Toyyib; Abd. Aziz (STIT Al - Ibrohimy Bangkalan, 2025)
This community service activity focuses on the discourse of methamphetamine prevention within the framework of youth education and empowerment. The purpose of the program was to provide information about the dangers of methamphetamine abuse and to offer preventive solutions targeting the youth of Tlagah Village, Galis Subdistrict, Bangkalan Regency. The methods used included educational presentations, interactive Q&A sessions, and a final evaluation. Although the program was not based on a research design with a formal hypothesis, it assumed that increasing awareness would lead to behavioral change among youth regarding drug use. The outcomes revealed that participants gained a better understanding of the dangers of methamphetamine and were able to identify preventive measures. This activity contributes to the fields of public health education and community empowerment. The findings highlight the importance of community-based outreach as an effective strategy for drug prevention at the grassroots level.